Energy Profiles of an Agricultural Frontier: The American Great Plains, 1860–2000 - Cunfer, Geoff (Reg Environ Change, 2017)
Agro-ecosystem energy profiles reveal energy flows into, within, and out of U.S. Great Plains farm communities across 140 years. This study evaluates external energy inputs such as human labor, machinery, fuel, and fertilizers. It tracks the energy content of land produce, including crops, grazed pasture, and firewood, and also accounts unharvested energy that remains available for wildlife. It estimates energy redirected through livestock feed into draft power, meat, and milk, and estimates the energy content of final produce available for local consumption or market sale. The article presents energy profiles for three case studies in Kansas in 1880, 1930, 1954, and 1997. Two energy transformations occurred during that time. The first, agricultural colonization, saw farm communities remake the landscape, turning native grassland into a mosaic of cropland and pasture, a process that reduced overall landscape energy productivity. A second energy transition occurred in the mid-twentieth century, characterized by fossil fuel energy imports. That outside energy raised harvested and unharvested energy flows, reused biomass energy, and also final produce. This socio-ecological transition increased landscape energy productivity by 33 to 45 percent above pre-settlement conditions in grain-growing regions. These energy developments were not uniform across the plains. Variations in rainfall and soil quality constrained or favored energy productivity in different places. The case studies reveal the spatial variation of energy profiles in Great Plains agro-ecosystems, while the longitudinal approach tracks temporal change.